Small bowel transplantation in children: an immunohistochemical study of intestinal grafts. - Fromont, G (1995)
Seven children with short bowel syndrome underwent small bowel allografting. Episodes of early rejection were observed in five patients who received a graft from paediatric or adult donors but not in two patients who received a neonatal graft. This study aimed, firstly, to define immunohistochemical parameters accompanying rejection and, secondly, to compare immunohistochemical parameters in neonatal grafts with those in grafts from older donors. An immunohistochemical analysis was performed on 85 intestinal biopsy specimens taken for monitoring the transplant. Acute histological rejection was associated with pericryptic infiltrates of CD3+TcR alpha beta + T cells containing clusters of CD8+ cells, numerous CD25+ cells, and increased numbers of CD68+ macrophages. These changes were associated with the appearance of major histocompatibility (MHC) class II antigens on crypt enterocytes and with an appreciable increase in the expression of E-selectin on mucosal endothelial cells. Immunohistochemistry was useful in predicting rejection by showing the appearance of pericryptic CD25+ T cells 48 hours before the first histological lesions of crypt necrosis. Comparison of neonatal grafts with grafts from older donors did not show any significant difference in the density of CD68+ macrophages or in the endothelial expression of intercellular adhesion molecule-1, vascular cell adhesion molecule-1, or E-selectin. In contrast to grafts from older donors, however, neonatal grafts did not express MHC class II antigens on epithelial cells and contained very low numbers of intraepithelial lymphocytes. These data indicate, firstly, that immunohistochemistry is useful for monitoring intestinal transplants and, secondly, that the better clinical tolerance of neonatal allografts may be related to the lower immunogenicity of the neonatal epithelium.